Analisis Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Pertumbuhan Ekonomi Kabupaten Pamekasan - Dewi, Irma Sulistia; Huda, Syamsul (Al-Buhuts, 2023)
This study aims to determine and analyze the effect of Regional Original Income, General Allocation Funds, and Special Allocation Funds on the Economic Growth of Pamekasan Regency. The secondary data used was obtained from BPS Pamekasan Regency from 2008 to 2021. The analysis used was multiple linear regression analysis using the BLUE Classical Assumption test with multiple linear analysis tests using the SPSS program. The results of the study show that there is an influence of regional original income and general allocation funds on economic growth, while special allocation funds have no effect on economic growth.